The Picture Word Inductive Model: Its Effectiveness to Teach Writing Viewed from Students' Interest - Rahayu Meliasari; Ngadiso Ngadiso; Sri Marmanto (Universitas Jambi, Magister Program of English Education Department, 2018)
Picture Word Inductive Model is an inquiry-oriented strategy for teaching writing that uses picture containing familiar objects to fully lead students into inquiring about words, adding words to their writing, and ultimately developing the title, sentences, and paragraphs about their picture. This experimental study aimed to find out the effectiveness of PWIM to teach writing viewed from students’ interest in the eighth grade of MTs. ASWAJA Pontianak. Sampling technique was through cluster random sampling resulting 2 classes which consist of 26 students of each class contributed to the study. Technique of data collection encompassed writing test and questionnaire. The data were analyzed by using 2x2 Multifactor Analysis of Variance (ANOVA) and Tukey’s HSD Test. The result revealed that: (1) Picture Word Inductive Model(PWIM) is more effective than Controlled-Writing Strategy (CWS) to teach writing; (2) students having high interest have better writing skill than those having low interest. (3) there is an interaction between teaching strategies and the level of interest on students’ writing skill.